1967
DOI: 10.1029/jz072i013p03483
|View full text |Cite
|
Sign up to set email alerts
|

Frothing as an explanation of the acceleration anomalies of cometary meteors

Abstract: It is suggested that fragmentation may not be the general explanation of the cometary meteor density anomaly. Observations, in ground laboratory facilities, show that terrestrial and extraterrestrial rock will froth during ablation, and the froth may subsequently be sloughed as a result of aerodynamic pressure forces. A new concept, based on these observations, is introduced to explain the density variations of some cometary meteors. Cometary meteor data are analyzed using the frothing‐sloughing concept to fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Toward the end of the test (again roughly 4 s), some material ended up smeared over the probe holder (see Figure 15 left). This effect looks very similar to what Allen named frothening of the meteorite material (Allen & Baldwin 1967) and it is similar to the behavior of the basalt sample. The essential difference is that for the EM132 sample this happened much faster.…”
Section: Ordinary Chondritesupporting
confidence: 82%
See 1 more Smart Citation
“…Toward the end of the test (again roughly 4 s), some material ended up smeared over the probe holder (see Figure 15 left). This effect looks very similar to what Allen named frothening of the meteorite material (Allen & Baldwin 1967) and it is similar to the behavior of the basalt sample. The essential difference is that for the EM132 sample this happened much faster.…”
Section: Ordinary Chondritesupporting
confidence: 82%
“…Melting of these samples in arc-jet testing was used to improve analytical tools for entry predictions of meteors (Allen & Baldwin 1967). Compared to these very early investigations, recent ground tests by Park et al in 2012 at the ballistic range at NASA Ames Research Center showed that, depending on the porosity of the meteor, fragmentation behavior can be very different (Park & Brown 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This results from differences in the resistance to ablation and breakup in the atmosphere, as well as weathering. The conjecture attributed by Allen and Baldwin [1967] to Carleton Moore that carbonaceous chondrite may be a common type of meteorold has received support. Keays et al [1970] have found an enrichment of trace elements in Apollo 11 lunar soil and type C breccias which they attribute primarily to a 1.5 to 2% admixture of carbonaceous-chondritelike material.…”
Section: Purpose Of the Present Investigationmentioning
confidence: 99%
“…Anomalously large increases in deceleration along the trajectories have been attributed to fragmentation of the structurally weak porous material [Jacchia, 1955;Jacchia et al, 1965]. The frothing-ablation model [Allen and Baldwin, 1967;Baldwin and Allen, 1968] was offered as an alternative interpretation in terms of originally solid meteoroids. In this view, accumulations on the entering body of low-density froth produced by heating in the atmosphere are partly responsible for the anomalous decelerations observed.…”
mentioning
confidence: 99%
“…Explanations are given for the phenomena of wake blending (persistent luminosity in the wake) and meteor trails that appear to begin abruptly [Jacchia et al, 1965]. Figure 1 illustrates some of the processes observed in are jet tests [Allen and Baldwin, 1967;Shepard et al, 1967] that are expected to occur also along a meteor trajectory. Lowdensity froth is produced in the heated region at the front and resolidifies on the sides.…”
mentioning
confidence: 99%